Characterization of patients diagnosed with squamous cell carcinoma of the anal canal. Cienfuegos, 2017-2019 - Yeidy Santos Toledo; Jorge Luis Estepa Pérez; José Antonio Feliú Rosa; Tahiluma Santana Pedraza; Daniel Alejandro Díaz Conde (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2021)
Background: squamous cell carcinoma of the anal canal constitutes a health problem of great magnitude, due to its high morbidity and mortality. The risk of suffering from this disease differs between individuals according to their modes and lifestyles. Objective: to characterize the patients diagnosed with squamous cell carcinoma of the anal canal in the Cienfuegos province from January the 1st, 2017 to December 31st, 2019. Methods: descriptive and prospective study on patients diagnosed with squamous cell carcinoma of the anal canal. The data were obtained from the medical records and the minutes of the deceased committee. The variables were analyzed: age, sex, skin color, associated diseases, clinical stages, form of presentation, classification of surgery, type of treatment, surgical technique used, cancer treatment, among others. The data obtained were processed using the SPSS version 21 statistical program; the results were showed in tables using absolute numbers and percentage. Results: female patients between 50 and 70 years old predominated; rectal bleeding and anal pain were the fundamental symptoms, accompanied or not by changes in bowel habit, straining and tenesmus; human papillomavirus was the most observed personal pathological history; the colostomy was the most widely used surgical technique. Conclusions: squamous cell carcinoma of the anal canal constitutes a health problem, associated with unprotected sexual life and sexually transmitted diseases; early diagnosis allows a better study and staging and therefore the use of more conservative surgical techniques.